Optimization of Occupational Safety and Health Management at PT Aplikanusa Lintasarta Makassar - Amsyir, Nur Shafira Ramadhani; Niswaty, Risma; Isgunandar, Isgunandar (ASHA Publishing, 2025)
Implementing safety and health management in the work environment is always necessary and should be a priority in every company. Occupational safety and health management ensures the well-being and protection of every worker in the workplace. In supporting productivity and achieving common goals, optimal K3 management optimization is needed. This study aims to examine the optimization of occupational safety and health management in the work environment of PT Aplikanusa Lintasarta Makassar. This research is qualitative. Data collection methods such as observation, interviews, and documentation are used to achieve the research objectives. The research participants consisted of five employees of PT Aplikanusa Lintasarta Makassar. The study results show that the management of occupational safety and health in the work environment of PT Aplikanusa Lintasarta Makassar is optimal, as evidenced by